The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0021-75572002000300012
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de recém-nascidos pré-termo pequenos para a idade gestacional

Abstract: A tendency of recovering weight and length related to preterm infants with adequate size and term newborns was observed. The head circumference showed an obvious and early recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
0
2
0
4
Order By: Relevance
“…On the other hand, Ornelas et al 49 found that the extrauterine growth rates of premature small for gestacional age and appropriate for gestational age infants differ and that small for gestational age infants have less inclined growth curves than appropriate for gestational age until the fortieth week. Ehrenkranz et al 50 reported that appropriate for gestational age infants and infants who did not develop severe morbidities had higher growth rates.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ornelas et al 49 found that the extrauterine growth rates of premature small for gestacional age and appropriate for gestational age infants differ and that small for gestational age infants have less inclined growth curves than appropriate for gestational age until the fortieth week. Ehrenkranz et al 50 reported that appropriate for gestational age infants and infants who did not develop severe morbidities had higher growth rates.…”
Section: Discussionmentioning
confidence: 99%
“…29 With special regard to weight, 21 Counts model reliably shows the changes that occur during the growth of preterm newborns: 30 weight loss, which occurs in the first week of life (range of 4 to 5 days) in all curves; birth weight recovery, which occurs between the second and third weeks (range of 16 to 19 days) and weight gain. Somatic growth dynamics is graphically similar for all birth weight categories.…”
Section: Discussionmentioning
confidence: 99%
“…É importante considerar que, para a população de recém-nascidos pequenos para a idade gestacional, houve dois períodos diferentes de coleta de dados, mas as características das duas amostras foram semelhantes, conforme demonstrado nas Tabelas 1 e 2, o que nos permitiu o agrupamento dessas duas populações. Comprimento (cm) Um dos aspectos interessantes da metodologia deste trabalho foi encontrar, entre os diferentes modelos matemáticos que fazem o ajustamento dos dados, o modelo de Count, que inicialmente foi estudado através do trabalho de Anchieta 22 e, posteriormente, reaplicado no trabalho de Ornelas 29 . O modelo de Count, principalmente para o peso 21 , capta de forma fidedigna as alterações que ocorrem durante o crescimento dos RNPT 30 : o período de perda de peso, que, para todas as curvas, encontra-se na primeira semana de vida (variando de 4 a 5 dias); o período de recuperação do peso de nascimento, que ocorre entre a segunda e terceira semana (variando de 16 a 19 dias); e o período de ascensão do peso.…”
Section: Discussionunclassified